2009
DOI: 10.1007/s11104-009-0199-3
|View full text |Cite
|
Sign up to set email alerts
|

Boron mobility in peanut (Arachis hypogaea L.)

Abstract: In most plant families, boron (B) is phloem immobile. For plants such as peanut which bury their fruit, the mechanism for B delivery and the B source for fruit and seed growth remains enigmatic. Therefore, this study aimed to establish evidence of B retranslocation in peanut and to identify its importance in plant development. In a sand culture experiment, the increase in B contents in new organs after B withdrawal and the corresponding decline in B contents in older organs was evidence of B redistribution. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…Clearly, the consistent pattern of increasing B in the shoot as the plants aged indicates a higher degree of B mobility, compared to Zn and Cu. Similar pattern of B translocation was found in soybean under non-drought condition (Ross et al 2006), as well as in peanut (Konsaeng et al 2010).…”
Section: Effects Of Treatment Type On the Shoot-grain Dynamics Of Znsupporting
confidence: 77%
“…Clearly, the consistent pattern of increasing B in the shoot as the plants aged indicates a higher degree of B mobility, compared to Zn and Cu. Similar pattern of B translocation was found in soybean under non-drought condition (Ross et al 2006), as well as in peanut (Konsaeng et al 2010).…”
Section: Effects Of Treatment Type On the Shoot-grain Dynamics Of Znsupporting
confidence: 77%
“…The mobility of B can also be affected by the plant nutritional status, considering that in plants cultivated under B deficiency, the mobility of this element is impaired in comparison with plants grown under B sufficiency, as reported by Konsaeng et al (2010) and Will et al (2011). These authors reported that plants cultivated under B deficiency have a limited mobility due to a rapid complexation of B into stable compounds in the cell wall, which reduces its availability for translocation in the organism; however, this might not be true for other species of plants.…”
Section: Introductionmentioning
confidence: 93%
“…The concentration of different polyols is variable among species (Bieleski, 1982), and through transgene processes, the introduction of a gene to increment the production of sorbitol is made possible, which consequently confers mobility to B, as reported for tobacco plants (Nicotiana tabacum L.) (Brown et al, 1999). Therefore, in plants containing high concentrations of polyols in their phloem, B can be considered mobile, like species of the Fabaceae family, such as soybean (Glycine max L.) (Will et al, 2011), white lupin (Lupinus albus L.) (Huang et al, 2008), peanut (Arachis hypogaea L.) (Konsaeng et al, 2010), and in members of other families, such as olive (Olea europaea) (Hegazi et al, 2018) and citrange (Citrus sinensis L.) (Wu et al, 2019). Cowpea belongs to the Fabaceae family, and thus, it is possible to infer that the phloem mobility of B might occur in this species; however, no studies were performed with this species to date.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies showed that foliar B application could improve B availability in leaves and increase the B concentration in leaves [ 14 , 17 , 33 , 35 , 36 , 37 ]. The fact that foliar B resupply increased the concentration of B in treated leaves as well as young leaves ( Figure 3 B and C) implies that foliar-applied B can be transported from mature leaves to young leaves or the reproductive organs via the phloem [ 14 , 18 , 38 , 39 , 40 , 41 , 42 ]. According to Stangoulis et al [ 23 ], B has moderate phloem mobility in oilseed rape, since limited amounts of borate can be translocated to the young tissues through binding with sucrose.…”
Section: Discussionmentioning
confidence: 99%